Early Modern Encounters with the Islamic East Performing Cultures - Schülting, Sabine 1965- (Transculturalisms, 1400-1700 Ser., 2016)
An exploration of early modern encounters between Christian Europe and the (Islamic) East from the perspective of performance studies and performativity theories, this collection focuses on the ways in which these cultural contacts were acted out on the real and metaphorical stages of theatre, literature, music, diplomacy and travel. The volume responds to the theatricalization of early modern politics, to contemporary anxieties about the tension between religious performance and belief, to the circulation of material objects in intercultural relations, and the eminent role of theatre and drama for the (re)imagination and negotiation of cultural difference. Contributors examine early modern encounters with and in the East using an innovative combination of literary and cultural theories. They stress the contingent nature of these contacts and demonstrate that they can be read as moments of potentiality in which the future of political and economic relations - as well as the players' cultural, religious and gender identities - are at stake.